Urinary biomarker evaluation for early detection of gentamycin-induced acute kidney injury. (January 2019) - Sun, Bo; Zhou, Xiaobing; Qu, Zhe; Sun, Li; Cheng, Guilin; Yang, Yanwei; Miao, Yufa; Chen, Xiaoguang; Li, Bo
Graphical abstract: Highlights: Gentamicin (40 mg/kg) exposure induced minimal or mild kidney injury in beagle dogs for consecutive 12-days. Blood urea nitrogen and serum creatinine had the inferior sensitivity and poor predictive value at the early stage of kidney injury. Urinary albumin and trefoil factor-3 demonstrated superior sensitivity and specificity for monitoring kidney injury (both AUCs = 1.000). Levels of urinary albumin and trefoil factor-3 were highly related to the degree of kidney injury (both Pearson's r = 0.887, P < 0.05). Abstract: Drug-induced acute kidney injury is a serious problem in drug development and clinical treatment. Thus, highly efficient and non-invasive urinary biomarkers are required to control and prevent drug-induced acute kidney injury. Expanding on a previous study, we evaluated 9 novel urinary biomarkers in beagles, which were treated with gentamycin at a dose of 40 mg/kg for 12 consecutive days. N -acetyl-β-D-glucosaminidase was detected with high sensitivity and specificity at the early stage of renal injury (Area under the ROC cure (AUC) = 0.929, 95%CI: 0.722–0.995, P < 0.05 vs. serum creatinine and blood urea nitrogen). More importantly, the results indicated that albumin and trefoil factor-3 were significantly increased 6 days after gentamycin injection (compared with the control group, both P < 0.05). Receiver operator characteristics analysis showed that the diagnostic value of these two biomarkers were both high (both AUCs=1.000; both 95% CI: 0.832–1.000; albumin or trefoil factor-3 vs. serum creatinine or blood urea nitrogen, both P < 0.05). Moreover, albumin and trefoil factor-3 levels were highly correlated to the degree of kidney injury (both Pearson's r > 0.8, P < 0.05). Our data indicate that albumin and trefoil factor-3 may have value in the early diagnosis of kidney injury in non-rodent species and may thus inspire the preclinical use of urinary biomarkers in drug-induced acute kidney injury.